Southeast Asian muslims in the era of globalization - Miichi, Ken; Farouk, Omar; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2015)
This volume investigates the appropriate position of Islam and opposing perceptions of Muslims in Southeast Asia. The contributors examine how Southeast Asian Muslims respond to globalization in their particular regional, national and local settings, and suggest global solutions for key local issues.
Keywords: Religion; Islam; Ethnology -- Asia; Political theory; Asia -- Politics and government; Sociology; Economic development